Effects of Photoperiod on Larval Diapause Termination in the Bamboo Borer, Omphisa fuscidentalis Hampson - Phakamas Subta (Science Faculty of Chiang Mai University, 2019)
The larval diapause termination in bamboo borer, Omphisa fuscidentalis is under the control of ecdysteroid hormone which can be induced by photoperiod. In this study, the effects of photoperiod on levels of ecdysteroid titer and the termination of larval diapause of O. fuscidentalis were investigated. The larval diapause was induced by two photoperiodic conditions (LD 2:22 and LD 18:6) following which pupation occurred. Percentage of pupation within 60 days of observation in LD 2:22 and LD 18:6 were 67% and 78%, respectively. The day of pupation was first observed during 19-36 days of observation while it was 43-65 days for larvae kept in the dark (control). The ecdysteroid titer of larvae under various photoperiodic conditions was measured by enzyme-linked immunosorbent assay (ELISA). The level of ecdysteroid titer of the larvae significantly increased on day 20 with LD 2:22 and day 15 with LD 18:6. The expression of ecdysone receptors, OfEcR-A mRNA and OfEcR-B1 mRNA, were performed. The expression of OfEcR-A mRNA for LD 2:22 or LD 18:6 were significantly higher than that in the control larvae after day 10 and OfEcR-B1 mRNA were significantly higher than that in the control larvae after day 5. This level correlated with the increment of ecdysteroid titer, suggesting that photoperiod induces larval diapause termination by increasing the ecdysteroid titer in hemolymph and OfEcR mRNA expression in the epidermis.